A comparison of the annual cycle of sea level in coastal areas from gridded satellite altimetry and tide gauges - Ruiz Etcheverry, Laura Agustina (2015)
In this work we compare the annual component of sea level variations derived from 478 worldwide- distributed tide gauges with the annual component computed from a weekly gridded multi-mission altimeter product. Gridded altimetry data products allow for spatio-temporal analyses that are not possible based on along-track altimetry data. However, a precise validation is necessary in the coastal region before the gridded data can be used. Results of the comparisons show that root-mean-square differences (RMSD) between the two datasets are r2 cm for 76.4% of the sites. RMSD higher than 4 cm are caused by narrow coastal currents, nearby river outflows or other local phenomena. A methodology is proposed to assess the accuracy of the seasonal component of the gridded altimeter product in regions with a low density net of tide gauges. As a case study it is shown that the Southwestern Atlantic coast is a suitable region to study the spatio-temporal variability of the annual cycle of sea level since RMSD be- tween annual altimetry data and in-situ data are lower than 2.1 cm.